In Vitro Inhibition of Pseudomonas aeruginosa Elastase by Metal-Chelating Peptide Derivatives - Kessler, Efrat (1982)
Pseudomonas aeruginosa elastase is a zinc metalloendopeptidase, probably responsible for the tissue destruction observed during infections with this organism. The elastase of a virulent Pseudomonas aeruginosa strain (Habs serotype 1) was isolated and found to have a molecular weight of 35,000; it readily degraded elastin and cartilage proteoglycans. A series of amino acid and peptide derivatives containing the metal-chelating moieties hydroxamate, phosphoryl, or thiol were synthesized and tested as potential inhibitors of the enzyme. Inhibition constants (K(i)s) for the compounds were determined with the chromophoric substrate furylacryloyl-glycyl-l-leucyl-l-alanine. The hydroxamic acid derivatives of benzyloxycarbonyl-glycine, benzyloxycarbonyl-l-leucine and benzyloxycarbonyl-l-phenylalanine had inhibition constants in the range of 11 to 28 μM. The 2-mercaptoacetyl derivatives of l-leucyl-d-phenylalanine and l-leucyl-l-phenylalanine had K(i) values of 34 and 1.5 μM, respectively, demonstrating the stereospecificity of the inhibition. The most potent inhibitors tested were 2- mercaptoacetyl-l-phenylalanyl-l-leucine and phosphoryl-l-leucyl-l-phenylala-nine (K(i) = 0.2 μM). Similar compounds lacking the metal-chelating moiety were about 3 orders of magnitude poorer inhibitors. When the inhibition of the enzyme activity towards azocasein, elastin, or cartilage was examined, inhibitor concentrations approximately 50-fold higher than the respective K(i)s were required to obtain 60 to 90% inhibition. Virtually complete inhibition was achieved with these substrates at inhibitor concentrations 500-fold higher than the respective K(i)s (0.1 to 14 mM). Although, 2-mercaptoacetyl-l-phenylalanyl-l-leucine and phosphoryl-l-leucyl-l-phenylalanine exhibited the same affinity to the enzyme, the latter was inferior in inhibiting cartilage proteoglycan degradation. 2-Mercaptoacetyl-l-phenylalanyl-l-leucine represents a class of potent elastase inhibitors that might prove useful in the management of P. aeruginosa infections.